2019
DOI: 10.5603/cj.a2017.0080
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of global hemostasis to therapeutic hypothermia in patients with out-of-hospital cardiac arrest: Thromboelastography study

Abstract: (Cardiol J 2019; 26, 1: 77-86)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…One potential mechanism behind the increased risk of bleeding in MTH-treated patients could be a decreased platelet count in blood serum persisting after re-warming. This is consistent with prior studies involving cooling patients [45] as well as coagulation disorders and most likely results from impaired production of clotting enzymes at temperatures below 32C, which was previously studied by our group and others [7,8].…”
Section: Discussionsupporting
confidence: 92%
“…One potential mechanism behind the increased risk of bleeding in MTH-treated patients could be a decreased platelet count in blood serum persisting after re-warming. This is consistent with prior studies involving cooling patients [45] as well as coagulation disorders and most likely results from impaired production of clotting enzymes at temperatures below 32C, which was previously studied by our group and others [7,8].…”
Section: Discussionsupporting
confidence: 92%
“…As both hemostatic pathways and physiological anticoagulant systems are affected, the ensuing balance between pro-and anticoagulant systems seems to prevent major clinical consequences such as major bleeding or thrombosis. 39 Animal studies in experimental posthypoxic hypothermia showed impairment of primary hemostasis, attenuated coagulation, and decreased activity of coagulation inhibitors. 40 Platelet function was more incisively studied in a series of 82 patients undergoing therapeutic cooling after out-of-hospital cardiac arrest, which confirmed an impairment of platelet function assessed by various techniques in hypothermic patients.…”
Section: Hemostasis and Hypothermiamentioning
confidence: 99%
“…43 A more precise study on coagulation function in 21 patients who were subjected to therapeutic cooling showed delayed clot formation, impaired clot stability, and enhanced endogenous fibrinolysis. 39 However, there is no evidence that even deep hypothermia causes an increased bleeding tendency. 38 Instead, there is some evidence that deep hypothermia may cause thrombotic complications, in particular at the site of catheters that are used to achieve the lowering of the body temperature.…”
Section: Hemostasis and Hypothermiamentioning
confidence: 99%
“…Hypothermia is known to induce coagulopathy, and this can have a significant impact on VHA output and interpretation. Several studies have shown that TEG ® measurements are significantly different from expected values in patients being treated for cardiac arrest with therapeutic hypothermia [110,114]. Similar effects have also been reported in neonates treated for hypothermia [115].…”
Section: Hypothermiamentioning
confidence: 75%